2023
DOI: 10.1097/prs.0000000000010479
|View full text |Cite
|
Sign up to set email alerts
|

“The Effects of Tranexamic Acid in Breast Surgery: A Systematic Review and Meta-Analysis”

Abstract: Background: Tranexamic acid (TXA) is used in trauma and surgical settings. Its role in reducing postoperative blood loss in breast surgery remains unclear. The primary objective of this study was to determine the effect of TXA on postoperative blood loss in breast surgery. Methods: Searches of the PubMed, Ovid MEDLINE, Embase, CINAHL, and Cochrane Central Register of Controlled Trials databases were performed from inception to April 3, 2020. Inclusion criteria were any retrospective reviews, prospective cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
1
0
0
Order By: Relevance
“…All studies included in our review showed decreased rates of drainage output. Our findings are similar to Calpin et al (Calpin et al 2023 ) and opposite to Huynh et al (Huynh et al 2023 ) previous meta-analyses regarding breast surgeries.…”
Section: Discussionsupporting
confidence: 80%
“…All studies included in our review showed decreased rates of drainage output. Our findings are similar to Calpin et al (Calpin et al 2023 ) and opposite to Huynh et al (Huynh et al 2023 ) previous meta-analyses regarding breast surgeries.…”
Section: Discussionsupporting
confidence: 80%
“…New recommendations on two frequently used adjuncts have been included this year. Tranexamic acid, applied either systemically or topically, has been shown to prevent hematoma and seroma in some studies, but the evidence is not conclusive (LoE 2b/B/AGO +/−) [70,71]. Topical application of nitroglycerin ointment in the setting of mastectomy with or without reconstruction significantly reduced skin and nipple necrosis rates in meta-analyses [72][73][74].…”
Section: Oncoplastic and Reconstructive Surgerymentioning
confidence: 99%
“…While extant research underscores the potential benefits of TXA, discrepancies exist, with some studies presenting conflicting findings regarding its efficacy in specific subsets of trauma patients, one study conducted a systematic review and bias-adjusted meta-analysis of RCTs, highlighting the significant reduction in the risk of death due to bleeding with TXA, without an increased risk of vascular occlusive events [ 7 ]. Conversely, another study emphasized the ongoing investigation into the optimal dosing and timing of TXA administration in non-trauma surgical populations, indicating the lack of conclusive evidence in this patient group [ 8 ]. These findings echo those of other reports in the literature, suggesting that the debate on TXA’s benefits in trauma injury surgeries remains unresolved [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%